Molecular phylogeny and postharvest morphology of petals in two major Nelumbo nucifera cultivars in Thailand - Salaemae, Nurainee; Takeda, Seiji; Kubo, Nakao; Kaewsuksaeng, Samak (Agriculture and Natural Resources, 2018)
Nelumbo nucifera is a symbolic flower of Buddhism and widely used for decoration in Asia. In most cases its buds are used as cut-flowers, which usually do not open and the outer petals turn black, leading to loss of visual quality and thus decreasing their economic value in markets. In Thailand, two major cultivars, Sattabongkot and Saddhabutra, are used and exported to foreign countries. To investigate the difference between these two cultivars, their molecular phylogeny and postharvest morphology were examined. Using 25 simple sequence repeat (SSR) markers, the cultivar Saddhabutra was very close to the cultivar Satabuto. These results showed a high bootstrap (BS) value of 96%. In contrast, lotus cultivars in Thailand including Sattabongkot and Saddhabutra, showed a BS value of 90%. Saddhabutra and Satabuto are classified in the same group with high similarity, whereas Sattabongkot shows relatively lower similarity. Petal blackening started earlier in Saddhabutra than Sattabongkot, indicating a vase-life difference among cultivars, with Sattabongkot and Saddhabutra having a vase life of 72 and 54 h, respectively. The epidermal cells of normal petals of Sattabongkot and Saddhabutra showed freshness and a round shape with turgid cells. The petal blackening was accompanied with a reduction of the area and perimeter in both cultivars. Sattabongkot had fewer stomata than Saddhabutra. The study provided a molecular classification of the Thailand lotus cultivars and provides a useful technique for the quantification of the postharvest quality of lotus cultivars.